Solubilidade de sais de carbonatos em misturas aquosas contendo monoetilenoglicol na presença de dióxido de carbono - Maniçoba, Naíra Sinara de Almeida (2017)
Throughout the exploitation and production process of oil and gas, gas hydrate formation can cause flow interruption of pipelines, compromising the safety and especially the operational productivity. This is the reason why thermodynamic inhibitors of gas hydrates formation, such as monoethyleneglycol (MEG), are injected into the system in order to guarantee process’ operational and economic viability. However, the association between MEG and formation water’s ions can result in the reduction of salt solubility, increasing the precipitation potential and contribute to the deposit scale deposit in oil pipelines. Eventually, this process may cause blockage of oil pipelines and result in the unit’s shut down as an outcome. The cost related to scale incidence can reach, in global scale, billions of dollars per year in the oil industry, therefore, research concerning to propitious conditions of precipitation, in addition to avoidance techniques of deposit formation are highlights in the oil production. Moreover, salt solubility data shown in this paper has fundamental importance in the contribution to optimize projects and operational procedure of MEG reclamation and regeneration units, which includes salt removal stage. The aim of this work has been to study the salt precipitation conditions based on monoethyleneglycol combined with strontium carbonate (SrCO3) and iron carbonate (FeCO3) aqueous systems, in the presence or absence of carbon dioxide (CO2), evaluating solubility. The methodology used consists in the application of the analytical static method to determination of solubility data in aqueous solutions, with variable concentration of MEG, within the interval from 0% to 100%, as well as under partial pressure of CO2, operating from 760 mmHg to 1520 mmHg (strontium carbonate system) or from 760 mmHg to 1210 mmHg (iron carbonate system). The behavior identified, based on salt solubility data analysis, demonstrates that the increase in MEG concentration contributes to a reduction in salt solubility in the system. Furthermore, it has been noticed that raising the partial pressure of CO2 promotes a reduction of solution’s pH level as well as increase CO2 dissolved in solution, leading to an increase in salt solubility and, consequently, reduction in the amount of precipitate in the system. Mathematic models such as Setchenov empirical correlation and logarithm of excess solubility’s approach were applied to experimental data with the purpose of explain the behavior observed. The correlations used demonstrated to be satisfactory with low dispersion between calculated and experimental data.